2013
DOI: 10.1016/j.biopsych.2012.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Tacr1 Gene Variation and Neurokinin 1 Receptor Expression Is Associated with Antagonist Efficacy in Genetically Selected Alcohol-Preferring Rats

Abstract: Background Genetic deletion or antagonism of the neurokinin 1 receptor (NK1R) decreases alcohol intake, alcohol reward, and stress-induced alcohol relapse in rodents, while TACR1 variation is associated with alcoholism in humans. Methods We used L822429, a specific antagonist with high affinity for the rat NK1R, and examined whether sensitivity to NK1R blockade is altered in alcohol-preferring (P) rats. Operant alcohol self-administration and progressive ratio responding were analyzed in P-rats and their fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 36 publications
4
48
0
Order By: Relevance
“…In addition, BECs and rewards were positively correlated for a 30 minute SA session. Moreover, we verified the validity of our new SA paradigm by confirming the findings of Schank and colleagues (Schank et al, 2011, Schank et al, 2013), which used a classic WD and saccharin fading procedure to illustrate that 30 mg/kg of the NK1 antagonist L822429 blocks stress-induced reinstatement, but not baseline SA, of 10% EtOH. This distinction is important, as it demonstrates the ability of our model to specifically assess primary reinforcement for EtOH.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, BECs and rewards were positively correlated for a 30 minute SA session. Moreover, we verified the validity of our new SA paradigm by confirming the findings of Schank and colleagues (Schank et al, 2011, Schank et al, 2013), which used a classic WD and saccharin fading procedure to illustrate that 30 mg/kg of the NK1 antagonist L822429 blocks stress-induced reinstatement, but not baseline SA, of 10% EtOH. This distinction is important, as it demonstrates the ability of our model to specifically assess primary reinforcement for EtOH.…”
Section: Discussionsupporting
confidence: 86%
“…For example, Schank and colleagues have demonstrated that while alcohol SA in non-dependent Wistar rats is unaffected by L822429, escalated EtOH SA in alcohol preferring (P) rats is suppressed by even moderate doses of the compound (15 mg/kg, i.p. ; Schank et al, 2011, Schank et al, 2013). In contrast, stress-induced reinstatement of EtOH seeking is attenuated by L822429 pretreatment in non-dependent Wistars at a dose of 30 mg/kg (Schank et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the NK 1 R seems to be particularly involved in the stressrelated aspects of alcohol consumption, as NK 1 R antagonism reduced stressinduced, but not cueinduced, reinstatement of alcohol seeking [143,144] and escalation of alcohol consumption [140]. Interestingly, it has recently been shown that the alcoholpreferring (P) rats, which are selectively bred for high alcohol preference, display increased sensi tivity to the effects of NK 1 R antagonism on alcohol selfadministration and motivation to work for alcohol compared with their Wistar parent strain [145]. What is more intriguing about the genetically selected P rats is that they show an upregulated NK 1 R system, that is, increased transcript levels of Tacr1 and Tac1 [145].…”
Section: Neurokinin Receptormentioning
confidence: 99%
“…Interestingly, it has recently been shown that the alcoholpreferring (P) rats, which are selectively bred for high alcohol preference, display increased sensi tivity to the effects of NK 1 R antagonism on alcohol selfadministration and motivation to work for alcohol compared with their Wistar parent strain [145]. What is more intriguing about the genetically selected P rats is that they show an upregulated NK 1 R system, that is, increased transcript levels of Tacr1 and Tac1 [145]. Furthermore, Schank and colleagues also showed the presence of a G-C SNP in the transcriptional start sequence for Tacr1 and an increased transcription fac tor binding in the presence of the C allele, indicative of increased transcriptional activation of Tacr1.…”
Section: Neurokinin Receptormentioning
confidence: 99%
“…A hypothesis that remained to be addressed, therefore, was whether NK1R antagonists, while leaving basal alcohol intake unaffected, could suppress escalated alcohol consumption. In support of this idea, NK1R antagonists suppress alcohol consumption in a high alcohol preferring line of mice (C57/BL6J, see preceding) and attenuate escalated alcohol self-administration in alcohol-preferring (P) rats but do not affect alcohol self-administration in nondependent, nonpreferring rats (Thorsell et al, 2010;Schank et al, 2011Schank et al, , 2013. It was also demonstrated that P rats show an upregulated NK1R system, as evidenced by increased transcript levels of the Tacr1 gene, as well as increased receptor binding in specific brain regions.…”
Section: Preclinical Findings In Rodent Models Of Drug Addictionmentioning
confidence: 87%